CONTRIBUTIONS OF SIMULATIONS FOR THE TEACHING OF INTERNATIONAL RELATIONS IN BRAZIL: AN ANALYSIS ON THE CASE OF THE UNIVERSITY DISCUSSION FORUM - Silva, Alexandre Freitas da [UNESP] (Fundacao Univ Tocantins, 2019)
In order to understand the application of simulations and its incidence in teaching, the work analyzes the case of Forum de Discussao Universitario (FDU), from FFC-UNESP. The objective is to provide a pedagogical view from a very applied model in international relations courses, highlight skills developed by the method and its role in professional formation in international relations. For this, The research uses the analysis of theoretical references, data about the courses of International Relations in Brazil and, mainly, of answers to a questionnaire applied to students who participated in the Forum de Discussao Universitario. The result demonstrates the validity of Simulations as a method of teaching and for the career of international relations analyst. The conclusion is the importance of the reflection on the teaching of the area of Brazil for its development as a sphere of knowledge and professional.
Keywords: Simulations; Teaching; International relations